IMPLEMENTASI KEBIJAKAN PUBLIK DALAM PENGELOLAAN DANA DESA DI KECAMATAN MARTAPURA KABUPATEN OGAN KOMERING ULU TIMUR - Raden Wijaya; Rezky Aprilia (Fakultas Politik Pemerintahan IPDN, 2020)
In implementing the village fund management public policy in Martapura Subdistrict, East Oku Regency, there are 3 villages namely Tanjung Kemala Barat, Kotabaru Barat, Keromongan which have experienced an increase in the number of poverty so that it is focused on managing village funds and factors that become obstacles in implementing public policies in management. village funds. And the research method used is qualitative by applying descriptive methods with an inductive approach. The implementation of the village fund public policy in its implementation there must be factors that become obstacles in managing village funds in Martapura District. This factor comes from within and outside the organization itself, such as the insufficient apparatus of the Martapura District in terms of quality and quantity. So that it will affect the results of village fund management in all villages in the Martapura District. The management of Village Funds in Martapura District has been implemented well and runs smoothly according to the provisions, although in improving the community's economy it has not been implemented optimally. Especially in 3 villages where there was an increase in poverty, this happened because the absorption of the village allocation funds was not right on target, village funds were mostly spent on physical development. The allocation of village funds for empowerment and development of human resources was the key to progress in increasing an independent economy.Keywords: village fund, implementation, policy